2013
DOI: 10.1007/s12185-013-1280-5
|View full text |Cite
|
Sign up to set email alerts
|

A randomized dose-escalation study to assess the safety, tolerability, and pharmacokinetics of ruxolitinib (INC424) in healthy Japanese volunteers

Abstract: Ruxolitinib (INC424), a potent and selective oral Janus kinase 1 and 2 inhibitor, was recently approved by the US food and drug administration for the treatment of intermediate or high-risk myelofibrosis. The safety, tolerability, and pharmacokinetics (PK) of ruxolitinib have been extensively evaluated in healthy subjects and patients. The present study is the first to investigate the PK and tolerability of ruxolitinib in the Japanese population. Forty subjects were randomized to receive single (10-100 mg) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…This hypothesis is fully supported by the fact that other drugs targeting the IL-6 pathway, such as the mAbs tocilizumab, sarilumab, and sirukumab, have been shown to reduce exposure of coadministrated drugs like simvastatin, midazolam, or omeprazole (Schmitt et al, 2011;Zhuang et al, 2015;Lee et al, 2017). Moreover, ruxolitinib concentrations required to counteract IL-6mediated suppression of P450s and drug transporters in vitro are in the 1.0-1.2 mM range, which is close to the range of ruxolitinib maximum plasma concentrations (C max ; 0.59-1.29 mM) reached in patients treated with the JAK inhibitor (Ogama et al, 2013). In addition, ruxolitinib in vitro effects toward IL-6-related P450 and transporter repression seem to be not transient, i.e., they lasted at least 72 hours in cultured human hepatocytes.…”
Section: Discussionmentioning
confidence: 58%
“…This hypothesis is fully supported by the fact that other drugs targeting the IL-6 pathway, such as the mAbs tocilizumab, sarilumab, and sirukumab, have been shown to reduce exposure of coadministrated drugs like simvastatin, midazolam, or omeprazole (Schmitt et al, 2011;Zhuang et al, 2015;Lee et al, 2017). Moreover, ruxolitinib concentrations required to counteract IL-6mediated suppression of P450s and drug transporters in vitro are in the 1.0-1.2 mM range, which is close to the range of ruxolitinib maximum plasma concentrations (C max ; 0.59-1.29 mM) reached in patients treated with the JAK inhibitor (Ogama et al, 2013). In addition, ruxolitinib in vitro effects toward IL-6-related P450 and transporter repression seem to be not transient, i.e., they lasted at least 72 hours in cultured human hepatocytes.…”
Section: Discussionmentioning
confidence: 58%
“…However, we have previously reported that short-term suppression of either pSTAT5 or JAK1/2 activity can restore the apoptosis anticancer barrier and reduce mammary tumor risk in mouse models [ 11 ]. Ruxolitinib is an FDA-approved small molecule inhibitor of JAK1/2 for the treatment of myelofibrosis and polycythemia vera; it has minimal significant side effects following short-term use in healthy individuals [ 63 66 ]. Therefore, we asked whether short-term ruxolitinib treatment could prevent mammary tumors in early lesion-bearing mice on risperidone.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 80% (156/195) of samples tested demonstrate IC 50 values for Rux + Ven <0.5 μM. Previously reported levels of each drug in plasma (ruxolitinib C max for 10 mg BID: 0.562 μM [5]; venetoclax C max for 400 mg QD: 2.51 μM [6]) suggest effective combination concentrations would be achievable in patients.…”
mentioning
confidence: 99%